Catabolism of Human Fibrinogen Fragment D in Normal Subjects and Patients with Liver Cirrhosis - Ardaillou, Nicole; Yvart, Jeannine; Bras, Philippe Le; Larrieu, Marie-José (Thrombosis and Haemostasis, 1980)
The catabolism of human fragment D, (FgD), obtained by plasmin digestion of fibrinogen has been investigated in normal subjects and patients with liver cirrhosis and the results compared with those obtained for fibrinogen (Fg). Fg was labelled with I-125 and Fg D with I-131 using the chloramine T method. The plasma disappearance curves of both labelled proteins fitted a two exponential curve. In controls the plasma clearance rate of Fg D was greater than that of Fg as shown by the marked difference between the half-lives of these two tracers: 8,9 and 83,5 hours for Fg D and Fg respectively. The fractional catabolic rate of Fg D was 3.38 times the plasma pool per day. In nine patients with liver cirrhosis, catabolism of Fg was not modified. In contrast, catabolism of Fg D was significantly reduced with a half life of 13.0 hours and a low fractional catabolic rate. These results suggest the role of the liver in the catabolism of Fg D in man.
Keywords: Catabolism; Fibrinogen degradation products; Fragment D; Liver cirrhosis